Pemeriksaan Pap Smear di lingkungan Universitas Wijaya Kusuma Surabaya sebagai upaya deteksi dini kanker serviks - Tjandra, Lusiani; Masfufatun, Masfufatun; Purbowati, Rini; Indahsari, Noer Kumala (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2023)
Based on data from the Global Burden Of Cancer Study (Globocan) in 2020, total cancer cases in Indonesia in 2020 reached 396,914 cases and total deaths of 234,511 cases and cervical cancer (cervix) ranks second with 36,633 cases or 9.2% of total cancer cases. The incidence of cervical cancer will greatly affect the lives of sufferers and their families and will also greatly affect the health financing sector by the government. Therefore, increasing efforts to treat cervical cancer, especially in the field of prevention and early detection, is needed by every party involved. The purpose of this activity is to improve women's reproductive health through Pap smear examination at Wijaya Kusuma University Surabaya as detection of cervical cancer. The webinar activity was held on 18 December 2020 online and the free Pap smear examination was held on 21 April 2021 at the UWKS polyclinic. The result of this activity is that webinar participants can feel how important it is to know early detection of cervical cancer and realize the importance of early detection in reproductive health. At the time of the free Pap smear, the participants received a Pap smear medical examination, the sample was taken by Skin and Genital Specialist and then the sample was examined by Anatomy Pathology Specialist. Next, participants who needed further consultation and treatment were conducted at the FK-UWKS polyclinic.